Fatigue at work: Professional illness of the 21th century: Prevention and consequences - Kostić Marina R. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2015)
Psychophysical capabilities of individuals in terms of work in the modern systems of today are not the only factor that their performance and achievement of results depend on. The context is much broader, starting from work conditions at their work place, through physical and climate factors, social environment and support, down to psychophysical status of an individual, his/her general work efficiency and risk from getting professional illnesses. Although the mechanisms and causes of fatigue occurring at work have long been a subject of study and interest in the area of psychophysiology of work, the fact is that to the day there has been no unique and generally accepted definition of fatigue, not only due to complex causes of its origin, but also due to complexity and diversity of its manifestations. Factors that are subject of study may be grouped into areas of contents of work, organization of work or work environment, and they significantly affect working ability and its misbalance, needs, capabilities and requirements to be met by an individual at a work place. Similarly to the concept of stress at work, fatigue as a reversible physiological occurrence manifests itself in physiological, i.e. health-related, psychological and professional areas, which in the long run affects total performance and efficiency of an individual, and results in unfit behavior, mental problems or physical illness. Keeping this in mind, it is important that a professional department and personnel management in organizations and institutions should react in a timely manner in order to prevent, detect and eliminate the factors that bring an individual at work to chronicle fatigue, therefore, to reduced performance and productivity at work.